The Development Model of Home Health Care in Context of River Side Community: A Case Study of Khlong Chanak Sub District Health Promotion Hospital, Mueang, Surat Thani - ศรเกษตริน, อติญาณ์; จันทรา, รุ่งนภา; หีตอัษร, ชุลีพร; ปาณะวัฒนพิสุทธิ์, สุภาเพ็ญ; แก้วอยู่, รวีวรรณ; คำดี, สัญญา (Ganesha Journal, 2019)
This research and development aimed to develop a Home Health Care model in context of river side community at Khlong Chanak, Mueang, Surat Thani and community’s need and to evaluate the effectiveness of the model. It was divided into 4 phases. Phase 1: Situation analysis aimed to evaluate real situation and needs of Home Health Care in context of river side community. Qualitative data were collected by reviewing documents and using semi-structured interview guideline. Key informant were 3 village health volunteers (VHV). Phase 2: A model development for Home Health Care in context of river side community aimed to develop the home health care model. The 3 experts approved the model about the advantage, the accuracy, the feasibility and the propriety. Phase 3: An application of the model in community. Phase 4: A study of model’s effectiveness by using checklist and home visiting nurses satisfaction form. Samples were home care teams. Data analysis used content analysis and percent. The results showed that a Home Health Care model in context of river side community was followed as a system theory of Bertalanffy that composed of input, process and outcome of Home Health Care. The model effectiveness were 100% of coverage rate for home health care service, 100% of received home visit for patients who were referred back to community, average hour of home visit was 6 hours/week and home visiting nurses satisfaction was moderate level (mean 8.60 of total score 10, SD 1.18).